Jewish-Christianity and the History of Judaism Collected Essays - Reed, Annette Yoshiko (Mohr Siebeck, 2018)
Judenchristentum und die Geschichte des Judentums.
PublicationDate: 20180723
Keywords: Peter -- Late Antiquity -- Infancy Gospels -- Apocrypha -- Religious Identity -- Gottesknechtstradition -- Syria -- Cyprus -- reception studies -- Pseudo-Clementines -- Christliche Dogmatik -- Apostle -- Neues Testament -- Kirchengeschichte -- Antike -- Antike Religionsgeschichte -- Array